Analisis Sistem Tata Cahaya pada Bangunan Gedung XYZ - Dewi, Nur Aida Puspa; Nugroho, Teguh Wiji; Wardhana, Alex Sandria Jaya; Damarwan, Eko Swi (Innovative: Journal Of Social Science Research, 2021)
This study analyzes the lighting system of XYZ Building based on the lighting standard SNI 6197:2020. Based on the measurement results, the majority of rooms have light intensity below the established standard. The primary contributing factors include the use of inappropriate lamp types, an insufficient number of lighting points, dark-colored walls that absorb light, and a lack of proper lamp maintenance. The analysis indicates that although the lighting power per square meter is relatively efficient, visual comfort is not achieved. Recommended improvements include replacing old lamps with high-intensity LED lights, adjusting the lamp layout, and changing wall colors to enhance light reflectivity. The implementation of these recommendations is expected to improve lighting quality, ensuring compliance with the established standards. This study provides a crucial foundation for improving lighting systems in similar buildings to enhance energy efficiency and user comfort.